Effect of thermal and non-thermal processing on Technofunctional, nutritional, safety and sensorial attributes of potato powder - Muhammad Waseem; Saeed Akhtar; Tariq Ismail; Tawfiq Alsulami; Muhammad Qamar; Dur-e-shahwar Sattar; Raheel Suleman; Wisha Saeed; Crossby Osei Tutu (Food Chemistry: X)
Potato is a highly nutritious staple food however, it also contains some antinutrients like alkaloids, phytates, tannins, oxalates as well as pesticide residues. Therefore, this study was conducted to reduce the loads of antinutrients and pesticides in potato powder (PP) using thermal and non-thermal processing techniques. Nutritional analysis revealed that the raw PP contained significantly (p < 0.05) higher magnitudes of dietary proteins (10.2 %), fibers (6.3 %), Na (50 mg/100 g), Ca (62 mg/100 g) and K (988 mg/100 g) when compared with the processed PP. The results demonstrated that all thermal and non-thermal processing techniques significantly reduced the antinutrients and pesticide residues. However, microwave heat treatment anticipated the highest reduction in alkaloids, oxalates, tannins and phytates contents from 60 to 14 mg/100 g (76 % reduction), 31–6 mg/100 g (80 % reduction), 91–15 mg/100 g (84 % reduction) and 45–8 mg/100 g (82 % reduction), respectively. Additionally, microwave heat processing also exhibited the highest decline in imidacloprid, cypermethrin, bifenthrin, chlorpyrifos and deltamethrin contents by 87 %, 76 %, 63 %, 79 % and 81 %, respectively. Later, microwave-treated PP (the most effective treatment) was used to develop unleavened flatbreads (i.e., chapatis) @ 2–10 %. Organoleptic evaluation of supplemented flatbreads suggested that 5 % supplementation with microwave treated PP has the highest overall acceptability. Therefore, it is concluded that thermal and non-thermal processing techniques are effective tools to reduce loads of antinutrients and pesticide burden in potatoes. Moreover, the study also suggests, PP can be efficiently used as natural food supplement for development of value-added foods.